BEYOND WORDS: BALANCING TOP-DOWN AND BOTTOM-UP SKILLS IN TASK-BASED LISTENING ASSESSMENT - Rakhimova Mardona Odilbek qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: The article Beyond Words: Balancing Top-Down and Bottom-Up Skills in Task-Based Listening Assessment examines the interplay between two essential dimensions of listening comprehension: bottom-up processing, which focuses on decoding linguistic elements such as sounds, vocabulary, and grammar, and top- down processing, which relies on background knowledge, prediction, and inference. It argues that listening assessment often emphasizes one skill at the expense of the other, leading to incomplete evaluations of learners’ proficiency. Through discussion of task- based assessment approaches, the article highlights how authentic tasks—such as information-gap activities, problem-solving discussions, and the use of real-world audio materials—can integrate both micro-level detail recognition and macro-level understanding. The article also outlines pedagogical implications, emphasizing authenticity, scaffolding, fairness, and meaningful feedback in assessment design. By advocating for a balanced framework, the work contributes to current debates in applied linguistics and assessment design, suggesting that effective listening assessment must go beyond isolated word recognition to measure holistic communicative competence.